PENINGKATAN KEMAMPUAN KETERAMPILAN MENULIS TEKS PROSEDUR DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI SIS - Anisa Dwi Hanifah; Yudi Hartono; Karni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve students writing’s skill outcomes through the application of the Serial Image Media in procedure text material in class V of SDN Sirapan 02 Madiun Regency for the 2024/2025 academic year. The research method used is Classroom Action Research (PTK) with the Kemmis and Mc model. Taggart is carried out in 2 cycles. Each cycle has four stages which include the planning stage, action implementation stage, observation stage, and finally the reflection stage. Data collection techniques from this research include observation techniques during the action phase and student learning outcomes tests. Then the data analysis technique for this research is quantitative and qualitative data analysis. Based on the data analysis that has been carried out, it can be concluded that the application of The Serial Image Media can improve the students writing’s skill of class V students at SDN Sirapan 02 Madiun Regency for the 2024/2025 academic year on Procedure Text. This can be seen from cycle I where the average gain value of 0.25 has not yet reached the research target, whereas in cycle II it has succeeded in achieving the agreed achievement target with a score above 75 with a moderate increase of 0.5.